Etički kodeksi i etika javnih službenika - Marčetić, Gordana (Institute for public administration, 2013)
Analiziraju se etičke mjere za hrvatske državne službenike nakon 1990. Pažnja je usmjerena na normativne i organizacijske aspekte koji uključuju tri mjere: zakonodavni okvir, Etički kodeks i tijelo za etiku. Prati se razvoj legislative i evaluira njegova primjena u praksi te ukazuje na nedostatak vrijednosne dimenzije u sadržaju hrvatskog Kodeksa. Raspravlja se o ulozi, ovlastima i poslovima Etičkog povjerenstva, povjerenika za etiku u središnjim tijelima državne uprave i Odjela za etiku pri Ministarstvu uprave. Daju se prijedlozi za poboljšanje etičkih mjera u državnoj službi. Prikazuje se i komparativna situacija u zemljama bivše Jugoslavije te nastanak, donositelje i sadržaj etičkih kodeksa proizašlih iz zajedničke upravne tradicije. U zaključku se ističe da su zakoni i kodeksi kao etičke mjere sami po sebi nedovoljni ako nisu internalizirani od onih koji ih primjenjuju i na koje se primjenjuju. Etičke kodekse ne treba poistovjećivati s pravnim propisima koji počivaju na mehanizmu prisile i sankcija niti bi ih trebala donositi zakonodavna i izvršna tijela, već sami javni službenici kao odraz internaliziranih vrijednosti i načela. The paper analyses the development of civil servants’ ethics in Croatia after 1990. There is a particular emphasis on the normative and organisational aspects of the issue, which include three interconnected measures recommended by the OECD: an effective legal framework, an implementable code of ethics, and a coordinative body in charge of ethical matters. The development of legislation in the field of ethics is described, followed by an evaluation of its implementation in practice. The lack of value dimension in the Croatian Code is pointed out. The paper proceeds to discuss the role, competences, and tasks of the Civil Servants’ Ethics Commission, as well as those of the individuals in charge of ethical matters in the central state administrative bodies and in the Ethics Department of the Ministry of Administration from their establishment onwards. In addition, the author makes suggestions for improvement of ethical measures in the Croatian Civil Service. There is an outline of the comparative situation in the countries at the territory of former Yugoslavia together with a description of the development, content and bodies competent for adopting of the codes of ethics, since Croatia and the other countries on that territory share the same historical circumstances and common administrative tradition. It is concluded that usefulness of laws and codes as ethical measures is insufficient unless they are internalised by the very servants. Thus, codes of ethics should not be compared to legal regulations that are based on the mechanism of force and sanctions nor should they be adopted by legislative and executive bodies, but by civil servants themselves as a reflection of internalised values and principles.